Estudo da Calogênese em Physalis peruviana L.: aspectos morfofisiológico, bioquímico, histológico e fitoquímico - Conceição, Isabela Souza Coccorese (2023)
Physalis peruviana L. has attracted the attention of consumers and the producer market for its versatility in consumption and phytotherapeutic potential, with the production of substances with proven actions. However, the content of compounds found in the plants is low for commercial exploitation, and there may also be alterations in the physicochemical characteristics due to environmental factors. In this sense, the culture of plant tissues enables the in vitro production of secondary metabolites, especially from callus, since it is possible to obtain a greater amount of plant material and allowing the sustainable exploitation of this species. Thus, the objective of this work was to promote callogenesis in different types of Physalis peruviana explants, characterizing their histomorphology and primary and secondary metabolism. For callus induction, leaves, cotyledons and hypocotyls were used in MS medium supplemented with different concentrations of 2,4-D and BAP, and subsequent analysis allowed choosing the hypocotyl explant supplemented with 1.11 μM of BAP and 9.00 µM of 2,4-D as the best treatment. The callus growth curve was plotted, with determination of fresh mass in an interval of seven days and demonstrated the presence of five phases. Following the growth curve, histological analysis was performed, which demonstrated meristemoids and constant presence of vascularization. Primary metabolites were also quantified, indicating a large amount of total soluble sugars and amino acids, and phytochemical screening was carried out, which attested to the presence of alkaloids and phenolic compounds.